2017
DOI: 10.1177/000313481708300937
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Management of Perforated Appendicitis in Children by Race and Insurance Status

Abstract: This study was conducted to assess whether race and socioeconomic status influence the management method used to treat pediatric perforated appendicitis. Nonelective pediatric admissions with a primary diagnosis of appendicitis were analyzed using data from the 2001–2010 Nationwide Inpatient Sample. Bivariate and multivariate analyses were used to determine the association between race, insurance status, median household income, rural/metropolitan location, and the risk adjusted odds of undergoing surgery, lap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Delays in diagnosis and treatment of surgical conditions are associated with increased health system costs and worse outcomes for patients . In acute appendicitis, racial and ethnic disparities occur in presentation, treatment, and outcomes . In children, delayed diagnosis may account for higher rates of perforation at presentation .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Delays in diagnosis and treatment of surgical conditions are associated with increased health system costs and worse outcomes for patients . In acute appendicitis, racial and ethnic disparities occur in presentation, treatment, and outcomes . In children, delayed diagnosis may account for higher rates of perforation at presentation .…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] In acute appendicitis, racial and ethnic disparities occur in presentation, treatment, and outcomes. [6][7][8][9][10] In children, delayed diagnosis may account for higher rates of perforation at presentation. 7,11 In a multicenter study by Goyal et al, 7 non-Hispanic Black children with appendicitis were more likely to have a delayed or missed diagnosis of appendicitis, less likely to undergo any imaging, and more likely to present with perforated appendicitis compared with non-Hispanic White children.…”
mentioning
confidence: 99%
“…Acute appendicitis may result in complications that endanger life. Appendicectomy is the communal accomplished emergency abdominal surgical procedure in various regions of the world [3][4] . Appendicectomy is mostly performed by young surgical residents in major part of the world.…”
Section: Introductionmentioning
confidence: 99%
“…Appendicitis is one of the most common emergencies in childhood, and the vast majority are treated surgically [1][2][3]. Approximately 7% of children presenting to emergency rooms with abdominal pain have acute appendicitis [4].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study utilizing disparities analytic files from 2015, 45% of pediatric appendicitis cases exhibited perforation as a major complication [2]. Hispanic and African American populations demonstrate an increased incidence of perforated appendicitis [3]. Ladd et al reported increased rates of complications in Hispanic versus African American children, regardless of timing of diagnosis [5].…”
Section: Introductionmentioning
confidence: 99%